UnTWISTing intestinal fibrosis: single-cell transcriptomics deciphers fibroblast heterogeneity, uncovers molecular pathways, and identifies therapeutic targets - Santacroce, Giovanni; Di Sabatino, Antonio (The Journal of clinical investigation, 2024)
Intestinal fibrosis is a severe complication of Crohn's disease, often requiring surgical intervention. Despite extensive research efforts, an effective treatment to prevent or reverse intestinal fibrosis remains elusive. In this issue of the JCI, Zhang, Wang, and colleagues employed single-cell RNA sequencing to uncover mechanisms of the fibrotic process. They identified a key fibroblast subset of TWIST1+FAP+ cells that interacts with CXCL9+ macrophages. TWIST1 emerged as a central regulator of the fibrotic microenvironment, representing a promising therapeutic target for effectively treating intestinal fibrosis.